ANALISIS EFEKTIVITAS PENERAPAN STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS KONSUMEN DI HOTEL SANTIKA BANGKA BELITUNG - Leonardo, Reno; Sitepu, Mimpin; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this study is to determine the influence of people, process and technology to consumer loyalty, either partially or simultaneously at Hotel Santika Bangka Belitung. The method used in this research is descriptive with quantitative approach with the intention to find correlation between independent variable with dependent variable by using statistic formula that is researching correlation influence of people, process and technology to consumers loyalty at Hotel Santika Bangka Belitung. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The sample in this study amounted to 115 people from the total population of 1564 people. The results of this study show that: (1) there is a significant influence among the people (employees) on consumer loyalty. This is proved by the value of t-count> t-table (4.383> 1.65845). (2) The result also shows that there is significant influence between process variable (process) to consumers loyalty. This is proved by the value of t-count> t-table (5.482> 2.01669). (3) The result of research indicates that there is significant influence between technology variable (technology) to consumers loyalty. This is proved by t-count> t-table (4.721> 1.65845). And (4) The result of research indicate that there are significant influence on people, process and technology variable to customer loyalty at Hotel Santika Bangka Belitung which is proved by Fcount (3,939)> Ftable (2,68).